Conventional or interpersonal communication: which works best in disseminating malaria information in an endemic rural Bangladeshi community? - Ahmed, Syed Masud; Hossain, Mohammad Shamim; Kabir, Moktadir (PloS One, 2016)
Includes bibliographical references (page 7-8).